The heart of the dragon - Colburn, George A.; Schwandt, Darrel (Nebraska : National Video Communications ; Lincoln : GPN [production company] ; Kuala Lumpur : Visual Resources [distributor], 1991)
Documentary about the history of China and their social life and customs. Also included their civilization
prog. 1. Reform in crisis : the aftermath of Tiananmen - prog. 2. Overview of chinese history - prog. 3. Legacy of Mao Zedong - prog. 4. Man & nature in China - prog. 5. Food & feasting in China - prog. 7. Communist ideology after Mao - prog. 8. Social control in Chinese society - prog. 9. China's legal system - prog. 10. Marriage & the chinese family - prog. 12. Social organization in China - prog. 14. Sources of social conflict in chinese society - prog. 15 Conflict resolution in contemp. chinese society - prog. 16. Peasant life in China - prog. 18. Industrial life in China - prog. 21. The open door policy - prog. 22 Intro. to chinese arts and literature - prog. 23 Intelectuals and the state - prog. 26 Facing the future : China approaches the 21st century
Executive producer, Jim Danielson
Host: Mike Chinoy
Keywords: Chinese; China -- History; China -- Civilization